Analysis of the Results of Drying Fish with Salt and without Salt using Sunlight - Aidil Fahmi Saragih; Erliska Pranandari; Siti Aisyah; Eka Sugiarti; Hikmah Setia Ningrum; Noni Audina Maisya; Eni Marta (Indonesian Journal of Multidisciplinary Science, 2022)
This research was carried out to analyze the results of drying fish with salt and fish without salt using sunlight. The subjects of this study were third-semester students of Non-Reg Campus STKIP Rokania. The research method employed in this study was descriptive qualitative research, which included interviews, observations, and data analysis. The process of drying fish with salt and fish without salt is not the same, according to the findings of the study; there is an additional salting procedure for drying fish with salt. Irregular sunlight makes the length of time the fish drying process cannot be determined. The results of drying fish with salt have dominant characteristics such as an oily texture, the color of the fish becomes white, and the fish has a salt odor. The characteristics of fish without salt have a hard texture, brownish color, and still have a fishy smell. Factors that affect drying time are sunlight, salt, and fish species. Handling fish such as drying fish needs to be done to prevent damage to fish quality.